(untitled) (Research, Society and Development, 2022)
Meat is considered one of the most important foods in the human diet, however it is an excellent means of contamination by pathogenic microorganisms due to its intrinsic characteristics. Considering salmonellosis as the major foodborne disease with the greatest impact on public health, the purpose of this study was to evaluate the microbiological quality of beef and chicken, isolating and identifying the existence of Salmonella sp. in pieces sold in several neighborhoods in the city of Mossoró-RN. To conduct the experiments, samples were acquired in 30 butcher shops (supermarket, grocery stores and public market) at random, since some neighborhoods had a higher concentration of establishments than others, especially the Santo Antônio neighborhood and the Paredões neighborhood (where locates the public market). Sixty samples were collected, 30 of beef (soft thigh) and 30 of chicken (breast). For detection of Salmonella sp., the procedures described in normative instruction No. 30 of 2018 were followed. As a result, a total of 18 (30%) positive samples were obtained for Salmonella sp. where 12 (20%) were chicken and 6 (10%) were beef. With this, it is concluded that there is a significant positive percentage in relation to the amount of samples analyzed, since these bacteria are considered a public health problem, making it necessary for greater attention by public agencies to control the quality of these products, since cases of contamination are associated with irregularities in the workspace, inadequate hygiene, storage errors and improper temperature.